Effect of morphology on the hydrogen storage capacity of sol-gel synthesized Ce-Y-O nanostructures. (1st August 2023) - Khaksar, Mandana; Dawi, Elmuez A.; Ganduh, Safaa H.; Jasim, Layth S.; Abdulsahib, Waleed K.; Mahdi, Makarim A.; Salavati-Niasari, Masoud
Abstract: Different morphologies of active materials affect hydrogen storage performance. Therefore, engineering the active materials through changes in synthesis conditions can result in changes in their size and morphology. A sol-gel process assisted by trimessic acid was used to synthesize the nanostructured Ce2 Y2 O7 . Five different morphologies were generated. Under the same conditions, charge-discharge chronopotentiometry tests were performed in order to compare the effect of Ce2 Y2 O7 nanostructures on hydrogen storage capacity in KOH electrolyte at a current of 1 mA. The results indicate that the highest capacity is attributed to the very thin nanoribbons (643 mAhg −1 ) while the lowest capacity is attributed to the agglomerated ribbons assembled with particles (276 mAhg −1 ). Graphical abstract: Unlabelled Image Highlights: Synthesis of Ce2 Y2 O7 nanostructures with different morphologies and sizes Sol-gel method used for engineering morphology by changing the synthesis parameters. Comparing the hydrogen storage capacity of synthesized samples with chronopotentiometry test The best performance is related to the Ce2 Y2 O7 with nanoribbons morphology (643 mAhg −1 ).